Detection of Infection with Larval Stages of Ornithobilharzia turkestanicum using PCR in Field-Collected Snails of Lymnaea gedrosiana from Northwestern Iran - Mohammad Yakhchali; Seyyed Yaser Mirrajei; Reza Malekzadeh-Viayeh (Iranian Journal of Parasitology, 2013)
Background: Infection with Ornithobilharzia turkestanicum has been reported in a wide range of animals worldwide. This study was undertaken to assess the util-ity of polymerase chain reaction (PCR), for detecting the infection with O. turke-stanicum larvae stages in Lymnaea gedrosiana.